2003
DOI: 10.1080/alp.37.1.10.13
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Topical Nitroglycerin and Transcutaneous Electrical Nerve Stimulation on Survival of Random-Pattern Skin Flaps in Rats

Abstract: We compared the efficacy of topical nitroglycerin and transcutaneous electrical nerve stimulation (TENS) on the survival of random-pattern skin flaps in rats. Thirty Wistar albino rats were used and a dorsal, cranially-based random-pattern flap was raised. The rats were divided into three groups of 10 rats each. The first group had only the flap raised while the second and third groups were given topical nitroglycerin 5 mg or TENS for one hour a day for seven days. The amount of flap necrosis was measured on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 15 publications
0
16
0
1
Order By: Relevance
“…34 Although the majority of animal studies have shown increased flap survival with the use of nitroglycerin ointment, three studies have shown a lack of benefit. 31,35,36 In all of these studies, the dose of nitroglycerin used was low (5 mg), which may be the reason a significant effect was not detected.…”
Section: Discussionmentioning
confidence: 91%
“…34 Although the majority of animal studies have shown increased flap survival with the use of nitroglycerin ointment, three studies have shown a lack of benefit. 31,35,36 In all of these studies, the dose of nitroglycerin used was low (5 mg), which may be the reason a significant effect was not detected.…”
Section: Discussionmentioning
confidence: 91%
“…Transcutaneous electrical nerve stimulation (TENS) is primarily used for the alleviation of pain and, in the previous animal and human studies, TENS has been shown to change local blood flow decreasing flap necrosis by activating neural fibers and modifying vascular resistance [1][2][3][4]. Patients treated with various cutaneous and fasciocutaneous flaps were included in the previous studies [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Landecker et al 2 verified that the treatment with retinoic and glycolic acids does not reduce the necrosis area, however, nicotinamide has shown some positive results according to Collins et al 3 Other drugs like nonivamide and nicoboxil, 4 recombinant human erythropoietin, 5 fibroblast growth factor, 6 nitroglycerin, and transcutaneous electrical nerve stimulation 7 have also been investigated, although, in some cases, it remains uncertain if they play a role in the repair of flap injury.…”
mentioning
confidence: 97%